Positive Academic Leadership: Stop Putting Out Fires; Start Making a Difference - Jeff Buller (Academic Chairpersons Conference Proceedings, 2017)
A highly interactive workshop on strategies that can help chairs move towards positive outcomes in even the most negative of situations, making their leadership more effective, effortless, and enjoyable.
Keywords: leadership positive management chair communication systems perspective